Sphingosine 1-phosphate in acute dengue infection. - Laksiri Gomes; Samitha Fernando; Randika Heshan Fernando; Nilanka Wickramasinghe; Narangoda Liyanage Ajantha Shyamali; Graham S Ogg; Gathsaurie Neelika Malavige (PLoS ONE)
Background Vascular leak is the hallmark of severe dengue infections and leads to complications such as shock and multi-organ failure. Although many mediators have been implicated in the vascular leak in dengue, the role of sphingosine 1-phosphate (S1P) has not been investigated. Metholodology/principal findings As S1P has been shown to be important in barrier integrity, we assessed the S1P levels in 28 patients with acute dengue and 12 healthy individuals. The S1P levels were significantly lower in patients with acute dengue (p = 0.002) and the levels in patients with grade IV dengue haemorrhagic fever (DHF) were significantly lower than those with dengue fever (p = 0.005). We then investigated the kinetics of S1P levels throughout the course of the illness in another 32 patients in serum samples obtained twice a day. We found that S1P levels were low throughout the course of illness and S1P levels were <0.5 µM in 12/23 patients with DHF when compared to 1/9 with DF. Conclusions/significance As S1P has shown to be important in the endothelial barrier integrity and increases transendothelial resistance, low levels of S1P in acute dengue infection are likely to contribute to increased vascular permeability.